Komisaris Independen sebagai Pemoderasi Pengaruh Leverage, Tipe Auditor, dan Kapitalisasi Pasar terhadap Intellectual Capital Disclosure - Muhammad Hadi Kusumah; Linda Agustina (Owner : Riset dan Jurnal Akuntansi, 2022)
The purpose of this study is to analyze the effect of leverage, the type of auditor, and market capitalization against Intellectual Capital Disclosure by moderated by independent commissioners. This study uses a quantitative method. The company included in the LQ45 index listed on the IDX in 2017-2019 a number of 102 was used as a population in this study. Purposive Sampling is a sampling technique and obtained 34 companies, so the research analysis unit was 102. The documentation method was used in this study as the data collection technique. Moderated regression analysis is used as a data analysis technique. Disclosure of Intellectual Capital Company LQ45 in 2017-2019 was obtained by an average of 60%. These results indicate the level of disclosure carried out by the LQ45 company in a high category. However, the government should make rules as a clear guideline regarding the disclosure of intellectual capital so that each company has clear guidelines to reveal the disclosure of intellectual capital and is encouraged to carry out wider disclosures.